Residual stresses in electron-beam coatings with a nitrogen-austenite matrix and structural mechanisms of their relaxation; The Physics of Metals and Metallography; Vol. 122, iss. 5 - Narkevich N. A.; Darenskaya E. A. Elena Anatolievna; Mironov Yu. P.; Smirnov A. I.; Durakov V. G.; Tagil’tseva D. N. (2011, 2011)
Title screen